DEI Strategy (Diversity, Equity, Inclusion) and Normative Commitment to Employee Performance with Knowledge Management Moderation at the Forwarding Company PT Wira Mitra Prima - Lukiyana, Lukiyana; Faa’is Ridhy Putra, Naufal (Dinasti Publisher, 2026)
This study aims to analyze the effect of Diversity, Equity, and Inclusion (DEI) strategies and normative commitment on employee performance, with knowledge management as a moderating variable at PT Wira Mitra Prima. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Square (PLS) and SmartPLS software, the research employed a causal design to test both direct and moderating effects among variables. The sample consisted of 100 employees selected through purposive sampling. The findings reveal that DEI strategies, normative commitment, and knowledge management each have a positive and significant impact on employee performance. Moreover, knowledge management was proven to strengthen the influence of DEI strategies and normative commitment, indicating that diversity initiatives and employee loyalty are more effective when supported by systematic knowledge sharing and application. These results highlight that integrating DEI policies, fostering normative commitment, and implementing effective knowledge management can sustainably improve productivity, efficiency, and performance quality. Despite its contributions, the study acknowledges limitations such as a relatively small sample size, short data collection period, and reliance on closed questionnaires, suggesting that future research should expand scope, sample, and include additional variables like job satisfaction, organizational culture, or leadership to enrich the model.